MEDIA CERPEN PADA KEMAMPUAN MENULIS PUISI SISWA KELAS X SMA MUHAMMADIYAH 9 BEKASI (STUDI EKSPERIMEN) - Rahmayanti, Indah (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2020)
This study aims to determine the effect of short story media on the ability towrite poetry class X students SMA Muhammadiyah 9 Bekasi. The experiment isdone, because students have a weakness in writing poetry. The research methodused Experiment Design. The design used is one group pretest-postest design thatis experiments conducted on one group only without comparison. The number ofsamples in this study amounted to 28 students in class X IPA. The results of thisstudy significant values 0.000 <0.05, then there is a significant difference in theability to write poetry before (pre-test) and after (post-test). So there is influenceof the use of short story media in improving the ability to write poetry class Xstudents. Results from the t-test after given the media treatment of short stories onthe results of writing poetry of 0.038 <0.05. Based on the results of research thatthe short story media influence the ability to write poetry students.